Information System Based On Attraction Of Travel Selfies And Intention To Visit Tourist Destinations In The Context Of A Study Of The Utilitarian And Hedonic Benefits Of Travel Selfies - Ardyan, Elia; Wijaya, Oscarius Yudhi Ari (Universitas Dharma Wacana, 2023)
Creating an information system based on travel selfie appeal and intention to visit tourist destinations involves integrating utilitarian and hedonic aspects to enhance user experience. Combining utilitarian and hedonic features, the information system aims to enhance the overall travel experience, from trip planning to enjoying the destination, while leveraging the appeal of travel selfies to create a more engaging and personalised platform. This study investigates the impact of utilitarian and hedonic advantages on the attractiveness of travel selfies and the intention to travel. There are 420 respondents from generation Z. The analysis employed is structural equation modeling, with Amos version 26 utilized to process the data. The findings of this study demonstrate that the utilitarian and hedonic effects of trip selfies can enhance their appeal. The appeal of travel selfies is a significant aspect of attracting travelers to travel destinations. Other research shows that hedonic benefits are more likely to get people to visit a site than utilitarian benefits. There are several implications presented both managerially and theoretically